Investigating the modulation of active preparation and passive dissipation on inhibitory control processes in the language switching paradigm - Shen, Qinfang (Frontiers in Psychology, 2023)
Previous language-switching studies have received scholastic attention and the observed switching cost patterns have provided empirical evidence for bilingual language control. However, results are inconsistent as the size of and (a)symmetry in switching costs differ across studies. In addition, there are various methodological differences that go beyond stimulus differences, such as the language proficiency of the participants (the participant-level factor) and the preparation time (a task-related level factor), which might be responsible for these inconsistent results. With a focus on task-related factors, the present study was designed to examine whether and how preparation time modulates the size and (a)symmetry in switching costs by using the language-switching paradigm. Replicating previous literature on language switching and task switching, a clear preparation effect was observed in all trials (stay and switch trials) for both L1 and L2. In other words, the switching costs were modulated by the cue-to-stimulus intervals, and specifically, switching costs decreased when the preparation time increased. Another intriguing finding was that even when participants were offered enough time to fully prepare for selecting the target language at the cue window, the switching costs were not completely eliminated. In terms of the passive preparation at the response-to-cue interval, switching costs could be modulated by the response-to-cue interval – the time for passive dissipation of inhibitory control applied in previous trials. The size of switching costs was clearly modulated by manipulating response-to-cue intervals and switching costs decreased as the waiting time after a naming response increased, suggesting that inhibitory control of the non-target language dissipated over time after the naming response.